Impact of Drug Administration Route on Drug Delivery and Distribution into the Lung: An Imaging Mass Spectrometry Approach. Issue 6 (December 2013) - Zecchi, Riccardo; Trevisani, Marcello; Pittelli, Maria; Pedretti, Pamela; Manni, Maria Elena; Pieraccini, Giuseppe; Pioselli, Barbara; Amadei, Francesco; Moneti, Gloriano; Catinella, Silvia
During the last decade, significant technological improvements in mass spectrometry have had a great impact on drug discovery. The development of matrix-assisted laser desorption/ionization imaging mass spectrometry (MALDI-IMS) has set a new frontier for the study of the distribution of endogenous and exogenous molecules present within a tissue. MALDI-IMS is a surface sampling technique that allows not only the detection of multiple analytes but also gives the spatial distribution of those analytes. Active compounds for pulmonary disease need an optimal and well-studied delivery into the lungs, in order to assure distribution with greater penetration into the peripheral or the alveolar region of the lung to maximize the therapeutic effects. IMS is very useful in the field of drug discovery, showing drug delivery and distribution in the body and organs. In this study, we present a comparison between two different ways of carrying out pulmonary drug administration: inhalation of a nebulized aerosol of aqueous drug solutions and intratracheal administration, which is much simpler, not expensive and commonly used during in vivo screening. Tiotropium bromide is a long-acting anticholinergic medicine used for maintenance treatment of chronic obstructive pulmonary disease. In the present work, tiotropium was administered by nebulization and by intratracheal instillation to guinea pigs at doses able to induce significant anti-bronchoconstrictive activity. Lung samples were dissected, frozen, cryosectioned and coated with matrix ( α -hydroxy-cinnamic acid). IMS analyses were performed using a MALDI-LTQ-Orbitrap XL. Using this technique we were able to compare different distributions of the drug depending on the method of administration.